Developing a Cryopreservation Protocol for Embryonic Axes of Six South American Peanut Genotypes (Arachis hypogaea L.) Using Desiccation–Vitrification - Tacán, M.; Andrango, R.; Tapia, C.; Sørensen, M.; Vollmer, R.; Pérez, C. (MDPI, 2024)
The present study investigates the cryopreservation of embryonic axes from the peanut genotype ECU-12466, demonstrating a successful protocol involving a 1 h desiccation on silica gel followed by a 1 h cryoprotection with Plant Vitrificatin Solution 2 (PVS2). The average dimensions of the excised embryonic axes were 5.6 mm in length and 3.5 mm in width, with plumule lengths averaging 2.2 mm. Notably, germination rates for cryopreserved axes ranged from 71.4% to 85.7%, showing resilience to varying desiccation and PVS2 treatment times, particularly at 1 h. Shoot length was significantly enhanced by a 1 h PVS2 exposure, while longer durations resulted in phytotoxic effects. Rooting rates were higher for samples treated with shorter desiccation periods, with 54% rooting achieved at 1 h of PVS2 exposure, contrasting sharply with just 16% at 2 h. The moisture content of the embryonic axes remained stable between 9.3% and 9.5%, indicating no detrimental impact from the applied treatments. To evaluate the protocol’s broader applicability, five additional peanut genotypes (ECU-11401, ECU-11418, ECU-11448, ECU-11469, and ECU-11494) were tested. While cryopreserved samples demonstrated high germination rates of up to 95.4% after 15 days, the rooting success was significantly lower (25.2%) compared to the control group’s 90.9%. Following transplantation, the growth performance varied among genotypes, with a success rate of 93% for ECU-11494. Overall, this study elucidates the critical parameters for optimizing cryopreservation protocols in peanut embryonic axes, contributing to more effective long-term conservation strategies.